Linguistic Dimensions of Branding: Morphological Structures in Tearoom and Coffeeshop Names - Abalkheel, Albatool (IJAS: International Journal of Arabic Studies, 2025)
This study investigates the evolution and significance of naming conventions for tearooms and coffeeshops, with a particular emphasis on morphological structures and cultural relevance. Over time, store names transitioned from generic descriptors to more creative and symbolic identifiers, reflecting a shift in consumer preferences and an evolution in branding strategies. The research highlights the critical role of a store's name in shaping consumer perceptions, influencing brand loyalty, and establishing market identity. A mixed-methods approach, including a survey of female undergraduate students in Qassim, Saudi Arabia, revealed distinct naming preferences, with coffeeshops favoring English and colloquial Arabic names, while tearooms lean towards Standard Arabic. The findings indicate a preference for triliteral Arabic names in coffeeshops, suggesting a trend towards simplicity and memorability, while tearooms often utilize culturally significant names. The study emphasizes the importance of linguistic characteristics—such as phonetics and semantics—in enhancing brand recall and consumer engagement. Ultimately, the research underscores the necessity for businesses to adopt culturally appropriate and memorable naming strategies to foster strong brand identities and consumer connections in a competitive marketplace. Future research avenues are suggested to explore morphological characteristics across diverse cultural contexts and industries.